Statistical mechanics of learning - Engel, A. (Andreas), 1957- (Cambridge University Press, 2001)
Artificial neural networks provide a simple framework for describing learning from examples. This coherent account of important concepts and techniques of statistical mechanics and their application to learning theory comes with background material in mathematics and physics, plus many examples and exercises, making it ideal for courses, self-teaching, or reference.